2008
DOI: 10.1073/pnas.0800739105
|View full text |Cite
|
Sign up to set email alerts
|

Functional specialization among insect chitinase family genes revealed by RNA interference

Abstract: The biological functions of individual members of the large family of chitinase-like proteins from the red flour beetle, Tribolium castaneum (Tc), were examined by using gene-specific RNAi. One chitinase, TcCHT5, was found to be required for pupal-adult molting only. A lethal phenotype was observed when the transcript level of TcCHT5 was down-regulated by injection of TcCHT5-specific dsRNA into larvae. The larvae had metamorphosed into pupae and then to pharate adults but did not complete adult eclosion. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
287
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(306 citation statements)
references
References 28 publications
11
287
1
1
Order By: Relevance
“…3B), we suspected that TcKnk might have a previously unrecognized function in protection of nascent cuticle from molting fluid, a role previously attributed exclusively to the envelope. We performed TcKnk RNAi and assessed whether the resulting chitin depletion could be rescued by simultaneous down-regulation of transcripts for either or both of the two chitinase-encoding genes TcCht-5 and TcCht-10 because these two genes have been shown to be critical for molting and turnover of chitin in the old cuticle (8). Remarkably, in agreement with the above hypothesis, confocal microscopy and quantitative chitin content analysis revealed that chitin levels could be restored to normal when both TcCht-5 and TcCht-10 were down-regulated along with TcKnk ( Fig.…”
Section: Tcknk Protects Cuticular Chitin From Degradation By Chitinasmentioning
confidence: 99%
See 1 more Smart Citation
“…3B), we suspected that TcKnk might have a previously unrecognized function in protection of nascent cuticle from molting fluid, a role previously attributed exclusively to the envelope. We performed TcKnk RNAi and assessed whether the resulting chitin depletion could be rescued by simultaneous down-regulation of transcripts for either or both of the two chitinase-encoding genes TcCht-5 and TcCht-10 because these two genes have been shown to be critical for molting and turnover of chitin in the old cuticle (8). Remarkably, in agreement with the above hypothesis, confocal microscopy and quantitative chitin content analysis revealed that chitin levels could be restored to normal when both TcCht-5 and TcCht-10 were down-regulated along with TcKnk ( Fig.…”
Section: Tcknk Protects Cuticular Chitin From Degradation By Chitinasmentioning
confidence: 99%
“…A finding that chitinolytic or proteolytic enzymes in molting fluid are excluded from the nascent procuticle would lend some support to the view that the envelope forms a barrier for protection of newly secreted layers of chitin or protein. Zheng et al (6) immunolocalized a chitinase in spruce budworm [orthologous to chitinase 5 of Tribolium castaneum (TcCht-5) (7,8)] in the molting fluid and the integument but did not determine whether this chitinase was colocalized with chitin in the newly synthesized cuticle. In this study, we refute the venerable notion that access of molting enzymes to nascent cuticle is restricted by the presence of a protective envelope and provide evidence for an entirely unexpected alternative mechanism.…”
mentioning
confidence: 99%
“…The phenomenon of RNAi has subsequently been described in a wide range of eukaryotic organisms including arthropods and mammals [40,45,48,77,100,121,147]. To date, RNAi has been used as a strategy to investigate gene function [5,15,213] (for example, it has been used to analysis the function of close to 17,000 of the 19,000 (approximate figure) genes in Caenorhabditis elegans [76,186]) and as an antiviral mechanism to combat viral infections in plants [182,211], invertebrates [29,185,209] and vertebrates (in particular, influenza, cancer and human immunodeficiency virus (HIV) [53,54,122,170,195].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to RNAi analysis, the spatiotemporal pattern of gene expression is determined via RT-PCR to ensure RNAi is performed at appropriate time points. Chitin/cuticle pathway genes, including those required for chitin synthesis (Arakane et al, 2005b;, molting, survival and fecundity (Arakane et al, 2010b;Arakane et al, 2009;Broehan et al, 2010;Hogenkamp et al, 2007;Zhu et al, 2008) and tanning of the epidermal cuticle (Arakane et al, 2010a;Arakane et al, 2009;Arakane et al, 2005a) have been functionally characterized, revealing a wealth of potential biotargets for arthropod-specific pest control. While the candidate gene approach has been of enormous value in T. castaneum, it imposes limitations due to reliance on sequence conservation.…”
Section: Red Flour Beetlementioning
confidence: 99%